(untitled) (Proceedings of the World Conference on Media and Mass Communication, 2024)
Cases of sexually transmitted infections (STIs) continue to rise at alarming rates worldwide. Numerous studies have outlined the disconnect between sex ed programs and the actual interests and concerns of the youth, causing them to seek these gaps in popular media. Given its immense popularity and diverse sexual health messages, the researchers sought to analyze the Netflix series “Sex Education” S3 and describe how it portrayed sexual health issues through the lens of Entman’s (1993) media framing typology: causation, consequence, problem, solution and responsibility. The study found that it addresses themes on identity, partner communication and sexual exploration, therapy as an effective method towards healing from sexual assault-related trauma, and idealized depictions of sex and human genitalia in pornography. Characters discuss STIs such as chlamydia, herpes, syphilis, and HIV, offering verbal insights regarding transmission, prevention, and treatment. The adolescent risk behaviors identified include engaging in casual relationships, unprotected sexual intercourse, having multiple sexual partners, and sexting. Unfortunately, framing analysis revealed that the consequences associated with these behaviors were notably absent. Rather than portraying unforeseen pregnancy as a problem or an immediate consequence, the show delves into the intricate psychosocial changes that unfold within the character as its result. Despite these, characters are framed as responsible for the prevention of teenage pregnancy and HIV through securing mutual consent, contraceptive use, and regular testing. The series also depicts media sensationalism and the conservative approach to sex education as institutional problems. While belittlement and inconsideration of teenage concerns, unnecessary disciplinary actions for voicing them, and public humiliation are framed as social problems. Overall, the show provides valuable insights into the multifaceted nature of teenage sexual health and well-being.